Students' Perception towards the Use of ICT in EFL Learning at Eleventh Grade SMA Negeri 1 Dolok Batu Nanggar - Herman; Ayu Widya Ningsih; Sihombing, Partohap Saut Raja; Silalahi, Dumaris E. (Universitas Nahdatul Ulama Surabaya, 2021)
This research aims at exploring high school students’ perception towards the use of ICT in EFL learning. To achieve the objective, 44 students at eleventh grade majoring in Language and Culture Science (IBB) SMA Negeri 1 Dolok Batu Nanggar located in Serbelawan were surveyed using questionnaire. The data obtained was analyzed by employing the descriptive analysis technique using questionnaire distributed to students in the form of Google Form. The results showed that the students’ perception was positive and high in each perception aspects in the questionnaire given. They are attractiveness, perceived effectiveness, and relevancy aspects that obtained index score of 86%, 84%, and 85% or categorized as strongly agree response, and 77% for perceived motivation aspects or categorized as agree response. Based on the result obtained, this study can be concluded that the use of ICT in EFL learning is attractive, effective, and relevant to the English material students need to learn. It also motivates students to learn English more.